Femoral vein wall thickness measurement: A new diagnostic tool for Behcet's disease - ALİBAZ ÖNER, FATMA; MUMCU, GONCA; DİRESKENELİ, RAFİ HANER; ERGUN, SAFİYE ATLAS TÜLİN (OXFORD UNIV PRESS, 2021)
Objectives. Diagnosing Behcet's disease (BD) is a challenge, especially in countries with a low prevalence. Recently, venous wall thickness (VWT) in lower extremities has been shown to be increased in BD patients. In this study, we aimed to investigate the diagnostic performance of common femoral vein (CFV) thickness measurement in BD and whether it can be used as a diagnostic tool. Methods.. Patients with BD (n=152), ankylosing spondylitis (n=27), systemic vasculitides (n=23), venous insufficiency (n=29), antiphospholipid syndrome (APS; n=43), deep vein thrombosis due to non-inflammatory causes (n=25) and healthy controls (n=51) were included in the study. Bilateral CFV thickness was measured with ultrasonography by a radiologist blinded to cases. Results. Bilateral CFV thickness was significantly increased in BD compared with all control groups (P < 0.001 for all). The area under the receiver operating characteristic curve for bilateral CFV thicknesses in all comparator groups was >0.95 for the cut-off value (0.5 mm). This cut-off value also performed well against all control groups with sensitivity rates >90%. The specificity rate was also >80% in all comparator groups except APS (positive predictive value: 79.2-76.5%, negative predictive value: 92-91.8% for right and left CFV, respectively). Conclusion. Increased CFV thickness is a distinctive feature of BD and is rarely present in healthy and diseased controls, except APS. Our results suggest that CFV thickness measurement with ultrasonography, a non-invasive radiological modality, can be a diagnostic tool for BD with sensitivity and the specificity rates higher than 80% for the cut-off value >= 0.5mm.
Keywords: Behcet's disease; ultrasonography; diagnostic; venous vascular imaging; RHEUMATOLOGY 1990 CRITERIA; CLASSIFICATION; INVOLVEMENT; THROMBOSIS